Brill Encyclopedia of Early Christianity Online (Brill, 2018)
The Brill Encyclopedia of Early Christianity focuses on the history of early Christian texts, authors, ideas. Its content is intended to bridge the gap between the fields of New Testament studies and patristics, covering the whole period of early Christianity up to 600 CE. The BEEC aims to provide a critical review of the methods used in Early Christian Studies and to update the historiography.